The Implementation of Higher Order Thinking Skills (Hots) in Malaysia Secondary School: Post PISA 2009 - Nabilah Abu Hassan, Fatin; Aqilah Mohamad, Quwwatun; Atika Mohd Rosli, Nurul; Talhah Ajmain@Jima‟ain, Muhammad; Khadijah Yusof Azuddin, Siti (International Journal of Psychosocial Rehabilitation, 2020)
In 2009, Malaysia decided to take part in the Programme for International Student Assessment (PISA) for the first time. PISA is an international survey that is conducted by the Organization for Economic Cooperation and Development (OECD), which aims to provide information regarding performances in education across countries, particularly in reading, mathematics, and science, through a special assessment. PISA is conducted every three years for groups of 15-year-olds in both OECD and non-OECD countries. Unfortunately, Malaysia showed poor performance in PISA 2009, as it was ranked in the bottom third in the overall ranking. This indicates that Malaysian secondary education students are lacking in terms of higher-order thinking skills (HOTS). The outcome of PISA 2009 has left a significant impact on the Malaysia Ministry of Education (MOE) in improving the current national education system. In 2011, the MOE launched the Malaysia Education Blueprint, which put greater emphasis on HOTS. This concept paper utilizes literature review for data collection. It will specifically discuss (1) various approaches outlined by the MOE in implementing HOTS in secondary education, (2) the ongoing progress, and (3) the feedback from the stakeholders on the implementation of HOTS.